ENVIRONMENTAL CORPORATE GOVERNANCE: CONTRIBUTIONS TO BUSINESS SUSTAINABILITY, EDUCATION AND PUBLIC POLICIES (International Seven Journal of Multidisciplinary, 2025)
Environmental corporate governance refers to the set of practices and policies implemented by companies and plays a fundamental role in mitigating environmental risks and complying with regulations. Corporate sustainability aims to promote practices that ensure a balance between economic growth, environmental preservation, and social well-being. Public policies are essential to fostering corporate sustainability, as they create a regulatory framework that guides corporate practices toward sustainable environmental and social goals. The overall objective is to analyze how the integration of these dimensions can strengthen sustainable corporate practices, improve environmental performance, and promote competitive advantage, aligning business operations with global demands for sustainability and responsibility. This research uses the narrative review method to investigate the contributions of Environmental Corporate Governance to corporate sustainability. In conclusion, the analysis showed that the integration of environmental practices into corporate strategies improves environmental performance and strengthens companies' competitiveness on the global stage. The results indicate that the implementation of effective public policies is essential to promote the transition toward a more sustainable business model.